Impacts of authentic texts on EFL students' reading comprehension - Millenia, Raihan Dwi Adinda; Mukhrizal, Mukhrizal; Sufiyandi, Sufiyandi (UNIB Press, 2024)
The purpose of this research was to explore the effect of authentic texts on students' reading comprehension of the English Education Study Program at the University of Bengkulu. This research applied a quantitative method, in the form of a quasi-experimental study. The subjects of the research were 68 sixth-semester students in which 34 students as the experimental group and 34 other students as the controlled group. The experimental group got treatment of authentic text, while the controlled group got treatment of textbooks. The instrument of the research used was the test. The mean score of the experimental group was higher than the scores of the controlled group (75.88: 68.24). The t-test calculation = (p<α); (0.005<0.05). It means alternative hypothesis was accepted, and null hypothesis was rejected. In other words, there was an effect of using authentic texts on students’ reading comprehension. It was recommended that it was a good idea for English lecturers, apart from other texts, pay close attention to authentic texts as well.